1983
DOI: 10.1111/j.2042-7158.1983.tb02902.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of perfusion rate on salicylate absorption in the rat

Abstract: The rate of flow of a drug solution down the gastrointestinal tract will influence the residence time at the absorption site and the permeability coefficient governing mass transport across the intestinal wall. Komiya et al (1980) examined the effect of fluid flow on the intestinal absorption of a number of steroids using the in-situ through-and-through rat intestinal perfusion technique. Their steady state results followed the physical model predictions described by:where C(I)/C(o) is the fraction of stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Ho et al (1983) showed that for progesterone the P ap p increased with flow rate, while in contrast, no effect was observed in the case of hydrocortisone. With the ionizable compounds, chlorothiazide and salicylic acid, the P app of the former increased with fluid flow while for the latter it appeared to decrease (O'Driscoll 1983). It was suggested that these effects were linked to pH changes affecting the degree of ionization (O'Driscoll & Corrigan 1983).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ho et al (1983) showed that for progesterone the P ap p increased with flow rate, while in contrast, no effect was observed in the case of hydrocortisone. With the ionizable compounds, chlorothiazide and salicylic acid, the P app of the former increased with fluid flow while for the latter it appeared to decrease (O'Driscoll 1983). It was suggested that these effects were linked to pH changes affecting the degree of ionization (O'Driscoll & Corrigan 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative mass transport models, which make different assumptions with respect to the experimental convection and diffusion conditions, including laminar flow, plug flow or perfect mixing tank models, may also be applied to determine the permeability coefficient . In practice different authors have used different perfusion fluid flow rates ranging from 0.1 to 4.0 mL min ¡1 O'Driscoll & Corrigan 1983; O'Reilly et al 1994; Lane et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations